HPV Vaccination Uptake, Hesitancy, and Refusal: Observations of Health-Care Professionals During the COVID-19 Pandemic. Issue 4 (28th July 2022) - Chido-Amajuoyi, Onyema Greg; Pande, Mala; Agbajogu, Constance; Yu, Robert K; Cunningham, Sonia; Shete, Sanjay
Abstract: HPV vaccination is highly effective at preventing several types of cancer; however, vaccine uptake is suboptimal. The COVID-19 pandemic has affected participation in cancer prevention measures such as HPV vaccination. To assess changes and barriers to HPV vaccination during the COVID-19 pandemic, we conducted a statewide cross-sectional survey of health-care professionals (HCPs) in Texas. Specifically, we evaluated changes observed by HCPs regarding HPV vaccination during the COVID-19 pandemic: 1) hesitancy, 2) refusal, and 3) uptake. Decreased HPV vaccination uptake were reported by 19.3% of HCPs, whereas increased HPV vaccination hesitancy and refusal were reported by 17.1% and 14.8% of HCPs in Texas, respectively. The COVID-19 pandemic had a negative impact on HPV vaccination. Our study identified barriers to HPV vaccination that are unique to the COVID-19 pandemic.